PERAN STAKEHOLDER TERHADAP PROGRAM KESEHATAN JIWA DALAM PENANGGULANGAN PASUNG PADA ORANG DENGAN GANGGUAN JIWA (ODGJ) DI KECAMATAN MOYUDAN KABUPATEN SLEMAN - Syifa Atun Nisa; Mubasysyir Hasanbasri; Nunung Priyatni (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2020)
Background: Mental health problems or mental health disorders are closely related to the physical restraint. Physical restraint on people with mental disorders is due to lack of information about mental health, financial barriers, inadequate access of mental health services especially in rural areas. The participation or role of stakeholder in mental health programs is one of the determinants to prevent the physical restraint on people with mental health disorders (ODGJ). Objective: This study aimed to find out and explore the role of stakeholders on mental health programs in prevention of physical restraint on people with mental health disorders in Moyudan, Sleman regency. Methods: This research was a descriptive study with qualitative methods. The research design used was a case study to identify and explore the role of each stakeholder in overcoming shackles in ODGJ in Moyudan District, Sleman Regency. The study used purposive sampling with research subjects totaling 19 people. Data collection is done by in-depth interviews, observation and document review. Results: All stakeholders have a role in mental health programs to prevent physical restraint on people with mental health disorders. Puskesmas as a key stakeholders have to advocate for other stakeholders. The results of advocacy are political commitment from local government, policy support from Health District Office, Social Welfare District Office, Ghrasia Mental Hospital, Moyudan district and village government. However, the implementation of the advocacy was not always successful. In this case, family as the main stake holder refused the advocacy. The negative stigma about mental health is one of the problem that is still difficult to deal within the community. Conclusion: All stakeholders have a role in mental health programs to prevent physical restraint on people with mental health disorders, although not yet optimal.